Co-processing methanol and ethanol in bio-char steam gasification for hydrogen-rich gas production. (27th July 2017) - Jia, Shuang; Ying, Hao; Sun, Yunjuan; Sun, Ning; Xu, Wei; Ning, Siyun
Abstract: Co-processing methanol and ethanol in bio-char steam gasification was investigated in a fixed-bed reactor. The effect of reaction temperature, steam flow rate and additives content on gas composition and H2 yield were evaluated. The results showed that bio-char is an ideal material for H2 production, and the maximum H2 yield (233.3 g/kg bio-char) was obtained in the absence of additives at 950 °C, 0.5 g/min steam flow rate, meantime, producing hydrogen-rich gas with slight formation of methane. Methanol and ethanol blended with steam, and subsequently introduced in reactor have positive effect on H2 yield. However, taking the economy and char conversion rate into consideration, 5 vol%–8 vol% may be suitable contents, and H2 yield increased to 342 g/kg and 308.9 g/kg with 5 vol% of methanol and ethanol added in gasifying agent at 950 °C and 0.5 g/min steam flow rate. Furthermore, the proposed catalytic gasification of hydrogen-rich gas for high purity hydrogen and synthetic natural gas may be a promising way for using the produced gases. Highlights: Co-processing methanol and ethanol in bio-char steam gasification was carried out. High H2 yield can be obtained by bio-char steam gasification. Methanol and ethanol enhanced H2 yield obviously. The low tar amount of syngas can be directly used in many applications.